Discriminate me - if you can! The Disappearance of the Gender Pay Gap among Public-Contest Selected Employees - Marina Töpfer; Carolina Castagnetti; Luisa Rosti (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes the effect of public-contest recruitment on earnings by gender using Italian labor market microdata. By decomposing the gender pay gap and accounting for double selection into employment and method of recruitment, we find that the gender pay gap vanishes, and even reverses among the young, when emplyoees are selected through a public contest. Since in such a case: a) selected employees (both women and men) possess higher productive characteristics than unselected ones; and b) the component referred to as 'discrimination' (either with or without selection) is no longer the main driver of the gap, our results suggest that public contests are merit-based and gender-fair screening devices. On the contrary, in general the Italian labor market appears gender biased, with a full-sample gender pay gap of 4%.
Keywords: J71; J13; J31; 330